RELATIONSHIP BETWEEN FOOD CONTACT TIME TO THE EFFECT ON TRANSFER OF MICROBES FROM CERAMIC FLOOR USING THE FIVE-SECOND RULE - Adityawardhana, Taufan; Widodo, Agung Dwi Wahyu; Rehatta, Nancy Margaritta (Journal of Community Medicine and Public Health Research, 2021)
Eosin-Methylene Blue (EMB) in order to isolate gram-negative bacteria (Escherichia coli) as the contamination level indicator. Microbes identified with gram staining and observed under a light microscope. The result  reported into 5 categories: microbes were founded or not in the petri dishes, determine whether lactose fermentation/acid production can be observed, grade the microbes concentration founded in the petri dishes (grade 1-6), classify the level of contamination (low-high), describing colonies shape in EMB agar and identifying the microbes with gram staining. The results was at the student center's canteen 3 of 5 samples under 5 seconds are positive and 5 of 7 samples until 300 seconds are positive. The level of contamination was inconsistent with increasing time. Whereas in the diagnostic center's canteen 12 of 12 samples were all positives, regardless of time. In conclusion, the five-second rule is a significant oversimplification of what actually happens when bacteria transfer from a surface to food. Risk of transfer of contamination is constantly present regardless of time.